2021
DOI: 10.3389/fpsyt.2021.692485
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Adaptive Coping Approaches to Self-Management From the Perspectives of Hospitalized Cardiovascular Patients: A Qualitative Study

Abstract: Objectives: This study aimed to explore the association between hospitalized cardiovascular patients' life events and adaptive coping approaches to self-management.Methods: The study was a qualitative study that was conducted in a cardiology department of one affiliated university hospital in Hangzhou, China. Twenty-eight participants with cardiovascular diseases were recruited through a purposive sampling procedure. Semi-structured interviews were used to gain insights into adaptive coping approaches to self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The subject of coping strategies was hardly discussed in contemporary literature of off-facility care of chronic disease patients, since the focus is more on the patients rather than the caregivers. Other previous studies [23,46,47] a rmed this and reported poor knowledge about coping strategies among caregivers. This may not only lead to poor care for the patients, it could lead to high level of psychological challenges to the caregivers resulting in further maladaptive behaviours like engaging in drug use.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The subject of coping strategies was hardly discussed in contemporary literature of off-facility care of chronic disease patients, since the focus is more on the patients rather than the caregivers. Other previous studies [23,46,47] a rmed this and reported poor knowledge about coping strategies among caregivers. This may not only lead to poor care for the patients, it could lead to high level of psychological challenges to the caregivers resulting in further maladaptive behaviours like engaging in drug use.…”
Section: Discussionsupporting
confidence: 57%
“…There is growing global recognition of how family care is complementing medical intervention in improving the health and quality of life of CVA survivors [12,17,18,21,22]. So far, there is signi cant agreement across literature [8, 9,18,23] a rming the e cacy of effective family support and care in improving the health quality of life of CVA survivors. Meanwhile, caring for CVA survivors can be labour and time intensive and pretty stressful, as the caregiver may have to contend with complex and sometimes unfamiliar instructions from the medical staff [11,18,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…The competency of self-management and digital skills affect patients’ decisions to accept CR referral. Additionally, previous studies provided an insight regarding coping mechanisms with three core elements of illness perceptions, cognition and regulation processing, and adaptive coping strategies ( 34 ). These factors have also been observed among patients in the post-AMI period.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review provided an overview of the core elements related to CR program process at different level of environments (institutional, individual, and interpersonal factors). With a summative review of previous study findings, the attitudes toward general self-management ( 32 ) and the adaptive coping strategies of Chinese cardiovascular patients ( 33 , 34 ) were extracted into the consideration of individual factors.…”
Section: Methodsmentioning
confidence: 99%
“…5,45 Notably, stressful life events in general may stimulate growth, adaptation, and building resilience in the face of adversity. 3,46 Cumulative lifetime adversity (experienced at a moderate level rather than no adversity or nonextreme high adversity) is associated with resilient responses to controlled stressors and is considered beneficial for achieving optimal well-being. 47 Newer measures capturing the cumulative effect of a range of stressful events (ie, lifetime adversity rather than recent or childhood experiences alone) may better account for the variation in resiliency over time.…”
Section: Limitationsmentioning
confidence: 99%